Bioactive compounds from callus culture of Elaeocarpus grandiflorus. (June 2020) - Habibah, N A; Nugrahaningsih, WH; Musafa, F; Rostriana, Y; Mukhtar, K; Wijawati, N; Anggraito, Y U
Abstract: E. grandiflorus has potential as a source of bioactive compounds. This study aims to analyze the content of flavonoid and phenolic bioactive compounds in the callus culture of E. grandiflorus in various concentrations of PGR. Callus culture induction was carried out by maintaining E. grandiflorus leaf stalk explants on solid Murashige & Skoog (MS) with the addition of growth regulators namely 2, 4-dichlorophenoxyacetic acid (2, 4-D) and picloram in different concentrations. The results of the study showed that callus maintained on MS medium with the addition of 2, 4-D and picloram could produce flavonoids and phenolics. Flavonoid and phenolic concentrations produced in each treatment varied. Overall, it can be concluded that the MS medium with additional growth regulators, 2, 4-dichlorophenoxyacetic acid (2, 4-D) or picloram can be used for bioactive compound production of callus Elaeocarpus grandiflorus .